2011
DOI: 10.1016/j.ejcts.2010.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Chest physiotherapy revisited: evaluation of its influence on the pulmonary morbidity after pulmonary resection

Abstract: Implementing a program of perioperative intensive chest physiotherapy reduced the overall pulmonary morbidity after lobectomy for lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 11 publications
1
31
0
5
Order By: Relevance
“…The overall incidence of PPC following thoracic surgery has been reported to vary from 15% to 37.5%, primarily due to the type of pulmonary complications studied, the clinical criteria used in the definition, and the type of lung surgery included [34]. Recent studies have reported a much lower incidence, ranging form 3.9% in the study by Reeve et al [35] to 12% in the Agostini et al study [36] (where PPC were defined as clinical or microbiological evidence of pulmonary infection requiring antibiotic therapy, or clinically significant atelectasis requiring bronchoscopy) to 15.5% and 4.7% respectively before and after implementing intensive physiotherapy in the report by Novoa et al [37]. Minor PPC are quite common and include unexplained fever, excessive bronchial secretions, abnormal breath sounds, and productive cough.…”
Section: Preventing Postoperative Pulmonary Complications (Ppc)mentioning
confidence: 96%
See 1 more Smart Citation
“…The overall incidence of PPC following thoracic surgery has been reported to vary from 15% to 37.5%, primarily due to the type of pulmonary complications studied, the clinical criteria used in the definition, and the type of lung surgery included [34]. Recent studies have reported a much lower incidence, ranging form 3.9% in the study by Reeve et al [35] to 12% in the Agostini et al study [36] (where PPC were defined as clinical or microbiological evidence of pulmonary infection requiring antibiotic therapy, or clinically significant atelectasis requiring bronchoscopy) to 15.5% and 4.7% respectively before and after implementing intensive physiotherapy in the report by Novoa et al [37]. Minor PPC are quite common and include unexplained fever, excessive bronchial secretions, abnormal breath sounds, and productive cough.…”
Section: Preventing Postoperative Pulmonary Complications (Ppc)mentioning
confidence: 96%
“…Agostini et al [53] demonstrated that physiotherapy either with or without incentive spirometry may reduce the incidence of PPC and improve lung function. Novoa et al [37] evaluated the role of perioperative chest physiotherapy in modifing the risk of pulmonary morbidity after lobectomy in 784 lung cancer patients (361 operated after implementing a new physiotherapy program). They reported that chest physiotherapy performed by specialized therapists reduced the overall pulmonary morbidity after lobectomy for lung cancer.…”
Section: Preventing Postoperative Pulmonary Complications (Ppc)mentioning
confidence: 99%
“…The aims of these programmes in critically ill patients are: to apply advanced costeffective therapeutic tools to decrease bed rest complications and patients' ventilator dependency; to improve residual function; to prevent the need for new hospitalisations; and to improve health status and quality of life [18][19][20]. Physical therapy in patients undergoing cardiac, upper abdominal and thoracic surgery may prevent and treat respiratory complications, such as secretion retention, atelectasis and pneumonia, by means of different techniques.…”
Section: Consequences Of Prolonged Mechanical Ventilationmentioning
confidence: 99%
“…폐절제술 환자의 수술 후 폐합병증 감소를 위해 조기이상을 포함 한 유산소 운동이 효과적인 것으로 보고된다 [7,8] 15.8% 감소시키고, 재원일수를 2.9일 단축시킨 것으로 나타났다 [10]. 그 러나 운동을 하더라도 운동의 강도가 너무 낮은 경우에는 운동능력 과 폐합병증에는 유의한 효과가 없는 듯하다 [11,12].…”
unclassified